Mutations in mitochondrial DNA regulate mitochondrial diseases and metastasis but do not regulate aging. (June 2016) - Hayashi, Jun-Ichi; Hashizume, Osamu; Ishikawa, Kaori; Shimizu, Akinori
Abstract : The mitochondria theory of aging proposes that accumulation of mitochondrial DNA (mtDNA) with pathogenic mutations, and the resultant respiration defects, are responsible not only for mitochondrial diseases but also for aging and age-associated disorders, including tumor development. This theory is partly supported by results obtained from our transmitochondrial mice (mito-mice), which harbour mtDNA with mutations that are orthologous to those found in patients with mitochondrial diseases: mito-mice express disease phenotypes only when they express respiration defects caused by accumulation of mutated mtDNA. With regard to tumor development, specific mtDNA mutations that induce reactive oxygen species (ROS) enhance malignant transformation of lung carcinoma cells to cells with high metastatic potential. However, age-associated respiration defects in elderly human fibroblasts are due not to mtDNA mutations but to epigenetic regulation of nuclear-coded genes, as indicated by the fact that normal respiratory function is restored by reprogramming of elderly fibroblasts.